Be aware of wires in the veins: a case of superior vena cava syndrome in a patient with permanent pacemaker - Agegnehu T. Gebreyes; Hom Nath Pant; Donna M. Williams; Sapna P. Kuehl (Greater Baltimore Medical Center, 2012)
Superior vena cava (SVC) syndrome is an unusual complication of pacemaker and implantable cardioverter–defibrillator implantation. It is believed to be due to SVC thrombosis with or without stenosis induced by endothelial disruption from repeated mechanical trauma by the leads. A 58-year-old man presented with gradual swelling of his face, neck, and upper extremities of 10 days duration. A pacemaker had been implanted for symptomatic bradycardia over 5 years ago. Venous Doppler and venogram revealed thrombosis and stenosis of the SVC. He was treated with multimodal therapy and was discharged with complete resolution of his symptoms.